Alterations of the Gut Microbiota in Response to Total Sleep Deprivation and Recovery Sleep in Rats - Wang Z; Yuan K; Ji YB; Li SX; Shi L; Wang Z; Zhou XY; Bao YP; Xie W; Han Y; Shi J; Lu L; et al. (Nature and Science of Sleep, 2022)
Zhong Wang,1,* Kai Yuan,1,* Yan-Bin Ji,2,* Su-Xia Li,3 Le Shi,1 Zhe Wang,1 Xin-Yu Zhou,4 Yan-Ping Bao,3 Wen Xie,5 Ying Han,3 Jie Shi,3 Lin Lu,1,3,6 Wei Yan,1 Wen-Hao Chen1 1Peking University Sixth Hospital, Peking University Institute of Mental Health, NHC Key Laboratory of Mental Health (Peking University), National Clinical Research Center for Mental Disorders (Peking University Sixth Hospital), Peking University, Beijing, 100191, People’s Republic of China; 2Department of Neurology, Qilu Hospital of Shandong University, Shandong University, Jinan, 250012, People’s Republic of China; 3National Institute on Drug Dependence and Beijing Key Laboratory of Drug Dependence, Peking University, Beijing, 100191, People’s Republic of China; 4Department of Psychiatry, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 5Mental Health Center of Anhui Province, Hefei, 230032, People’s Republic of China; 6Peking-Tsinghua Center for Life Sciences and PKU-IDG/McGovern Institute for Brain Research, Peking University, Beijing, 100871, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wen-Hao Chen; Wei Yan Peking University Sixth Hospital/Peking University Institute of Mental Health, 51 Huayuanbei Road, Haidian District, Beijing, 100191, People’s Republic of ChinaTel +86-10-82801342; Tel +86-10-62723704Email chenwenhao@bjmu.edu.cn; weiyan@bjmu.edu.cnIntroduction: Accumulating evidence suggests that both sleep loss and gut dysbiosis can lead to metabolic disorders. However, less is known about the impact of total sleep deprivation (SD) and sleep recovery on the composition, function, and metabolic dynamics of the gut microbiota.Methods: Specific-pathogen free Sprague–Dawley rats were subjected to 48 h of SD with gentle handling and then allowed to recover for 1 week. Taxonomic profiles of fecal microbiota were obtained at baseline, 24 h of SD, 48 h of SD, and 1 week of recovery. We used 16S rRNA gene sequencing to analyze the gut microbial composition and function and further characterize microbiota-derived metabolites in rats.Results: The microbiota composition analysis revealed that gut microbial composition and metabolites did not change in the rats after 24 h of SD but were significantly altered after 48 h of SD. These changes were reversible after 1 week of sleep recovery. A functional analysis was performed based on Kyoto Encyclopedia of Genes and Genomes (KEGG) annotations, indicating that 19 KEGG pathways were significantly altered in the gut microbiota in SD rats. These functional changes occurred within 24 h of SD, were more apparent after 48 h of SD, and did not fully recover after 1 week of sleep recovery.Conclusion: These results indicate that acute total SD leads to significant compositional and functional changes in the gut microbiota, and these changes are reversible.Keywords: gut microbiota, sleep deprivation, short-chain fatty acid, function prediction